Effect of Supplementation of Acidifiers with Probiotic on Performance of Broiler Chicken - Jadhao, G. M.; Wankhede, S. M.; Rekhate, D. H.; Dhok, A. P.; Bankar, P. S.; Rewatkar, H. N. (Indian Journal of Animal Nutrition, 2019)
An experiment was conducted to study the effect of supplementation of acidifiers with probiotic on performance and nitrogen retention of broiler chicken. A total 300 broilers were reared for six weeks with dietary treatments, T0 (control diet as per BIS, 2007), T1 (control plus sodium-diformate @ 0.2%), T2 (control plus sodium diformate @ 0.2% plus probiotic @ 0.02%), T3 (control plus blends of acidifiers @ 0.2%), T4 (control plus blends acidifiers @ 0.2% plus probiotic @ 0.02%). Each treatment consisted of sixty birds with four replicates containing fifteen birds in each replication. The weekly body weight, body weight gain, feed conversion efficiency was found to be better in all treatment groups as compared to control. However, weekly feed consumption, cumulative feed consumption was found to be unaffected. Also, there is increase in dry matter digestibility and nitrogen retention in all treatment groups as compared to control. It was concluded that the blends of acidifiers @ 0.2% in combination with probiotic @ 0.02% found to be economical in broiler raring.Â